Cantrell Syndrome. Case report of an adult - Falcão,João Luiz Alencar Araripe (2000)
Cantrell syndrome is characterized by defects that involve the diaphragm, abdominal wall, pericardium, heart, and lower region of the sternum. It is a rare entity, usually diagnosed at birth and accompanied by high mortality due to the complexity and gravity of the anomalies. In this report, we present a 32-year-old male patient, who was diagnosed in infancy but who reached adult age asymptomatic.